2020
DOI: 10.3390/antibiotics9020071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Ceftazidime-Avibactam for the Treatment of Infections due to Multidrug-Resistant Gram-Negative Bacteria Other than Carbapenem-Resistant Enterobacterales

Abstract: Background: Experience in real clinical practice with ceftazidime-avibactam for the treatment of serious infections due to gram−negative bacteria (GNB) other than carbapenem-resistant Enterobacterales (CRE) is very limited. Methods: We carried out a retrospective multicenter study of patients hospitalized in 13 Italian hospitals who received ≥72 h of ceftazidime-avibactam for GNB other than CRE to assess the rates of clinical success, resistance development, and occurrence of adverse events. Results: Ceftazidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 34 publications
3
60
2
3
Order By: Relevance
“…All of these organisms are defined as multidrug-resistant gram-negative bacteria and well-known pathogens responsible for nosocomial infections. These infections are most probably resistant to vancomycin and occur particularly in patients in ICUs [ 13 , 14 ]. The reason for the predominance of these bacteria might be due to the fact that five of the six patients in our study who developed post-operative SSI had follow-ups in the ICU in the early post-operative period.…”
Section: Discussionmentioning
confidence: 99%
“…All of these organisms are defined as multidrug-resistant gram-negative bacteria and well-known pathogens responsible for nosocomial infections. These infections are most probably resistant to vancomycin and occur particularly in patients in ICUs [ 13 , 14 ]. The reason for the predominance of these bacteria might be due to the fact that five of the six patients in our study who developed post-operative SSI had follow-ups in the ICU in the early post-operative period.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter retrospective study performed in Italy between 2016 and 2019 revealed a high clinical success rate in patients who received ceftolozane-tazobactam in empiric and/or targeted therapy for severe infections [ 176 ]. Concerning new drugs for a carbapenem-sparing approach, a recent real-life study assessed the role of ceftazidime-avibactam for the targeted treatment of patients with ESBL-E infections in selected cases, but the small study sample limited the drawing of definitive conclusions [ 177 ].…”
Section: β-Lactamase-mediated Resistance In Enterobactermentioning
confidence: 99%
“…Ceftazidima/avibactam, con registro sanitario en Chile desde julio de 2019 14 , y aprobación por el Instituto de Salud Pública de las cuatro indicaciones de la EMA, es una combinación novel donde avibactam tiene actividad contra las enzimas β-lactamasas de la clase A y la clase C según Ambler, incluidas las enzimas β-lactamasas de espectro extendido (BLEEs), las carbapenemasas KPC y las enzimas AmpC; y también sobre la carbapenemasa OXA-48 de la clase D 15 .…”
Section: Antimicrobianosunclassified